Geometry learning innovation based on ethnomathematics-collaborative augmented reality to improve elementary school students' metacognitive abilities: A conceptual framework - Jampel, I Nyoman; Utami, Ketut Herya Darma; Suarjana, I Made; Sukmana, Adrianus I Wayan Ilia Yuda; Suniasih, Ni Wayan; Antara, I Gede Wahyu Suwela (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze and describe the conceptual framework of the integration between ethnomathematics and Collaborative Augmented Reality (CAR) in geometry learning to improve elementary school students' metacognitive abilities. The approach used in this study is qualitative with an exploratory design. The participants of the study were 20 elementary school teachers in Bali who were selected purposively, considering the rich Balinese culture and traditions as contextual sources for ethnomathematics. Data were collected through Focus Group Discussions (FGD) and in-depth interviews, then analyzed using thematic methods. The results showed that the integration of ethnomathematics, which includes contextual basis, analytical thinking, meaningful learning, and reflective awareness, with CAR, which emphasizes visual exploration, critical thinking, active learning, and collaborative problem solving, significantly contributed to improving students' metacognitive abilities, especially in the aspects of self-regulation and self-reflection. Ethnomathematics facilitates more contextual and meaningful geometry learning, while CAR supports visual exploration and collaboration in problem solving. The integration of these two approaches results in interactive and reflective learning, improving students' metacognitive thinking skills in the context of geometry learning. Teachers can apply ethnomathematics combined with Collaborative Augmented Reality to create interactive geometry lessons that enhance students’ metacognitive self-regulation and reflection.